Accelerated corrosion solution and method for detecting resistance change rate and corrosion rate of flexible graphite grounding material by using accelerated corrosion solution
An accelerated corrosion solution using HCl, NaCl, NaNO3, and K2S2O8 in distilled water rapidly evaluates flexible graphite grounding materials, addressing the inefficiencies of existing methods by providing consistent and rapid corrosion resistance assessment.
Patent Information
- Application Number
- CN202411160139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-27
AI Technical Summary
Existing methods for evaluating the corrosion resistance of flexible graphite grounding materials are too slow and resource-intensive, failing to meet the needs of rapid detection and screening in power systems.
An accelerated corrosion solution comprising 2-7% HCl, 2-8% NaCl, 0.1-1% NaNO3, and 1-3% K2S2O8 in distilled water is used to immerse the materials for 8-15 hours at 25-50°C, followed by washing and drying, allowing calculation of resistance and mass changes to determine corrosion rates.
The method significantly accelerates corrosion evaluation, providing reliable results within 10 hours, consistent with traditional 30-day salt spray tests, and identifies materials prone to corrosion.
Smart Images

Figure CN119198511A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of performance evaluation technology, specifically to an accelerated corrosion solution and a method for detecting the resistance change rate and corrosion rate of flexible graphite grounding materials using the accelerated corrosion solution. Background Art
[0002] Grounding materials connect electrical equipment by burying conductors in the soil. When a power system experiences a large current surge due to lightning strikes, short circuits, or other emergencies, the grounding material can promptly conduct this current into the earth, effectively controlling overvoltages caused by the sudden accident and ensuring the safety of electrical equipment and personnel. There are many types of grounding materials, with commonly used ones including low-carbon steel, galvanized copper, and copper-clad steel. Flexible graphite is a new type of non-metallic grounding material developed in recent years, possessing advantages such as good conductivity, excellent corrosion resistance, and high current discharge efficiency.
[0003] Flexible graphite grounding materials are composed of an inner metal substrate (copper or stainless steel) and an outer graphite braided mesh. The internal structure significantly impacts their DC resistance, mechanical strength, corrosion resistance, and power frequency current withstand performance. A wide variety of flexible graphite grounding materials are available on the market, including cylindrical types with diameters ranging from 18 to 30 mm, and flat strip types in various specifications such as 40×5, 50×5, 50×8, 60×5, 60×8, and 60×12. While these products are generally similar in appearance, their internal metal substrates vary considerably, with some even lacking a metal substrate altogether. Product quality is inconsistent, with resistance per meter ranging from μΩ to mΩ, and significant differences in mechanical strength and aging corrosion resistance. Therefore, conducting corrosion resistance evaluations of flexible graphite grounding materials and performing rapid on-site testing before burial is crucial for eliminating substandard materials and ensuring the quality and service life of flexible graphite grounding materials.
[0004] To ensure the safety and reliability of the grounding system, corrosion resistance assessments of grounding materials are necessary before burying them. Testing methods for grounding material corrosion are mainly divided into two categories: on-site buried soil corrosion tests and indoor simulated corrosion tests. While on-site buried tests can objectively reflect the soil corrosion status at the burial site, the testing cycle is long and requires significant manpower and resources. Accelerated corrosion testing is a method that artificially controls test conditions to accelerate the corrosion rate. The most commonly used method is the salt spray test (GB / T10125-2012 / ISO 9227:2006). Although this method greatly shortens the corrosion time, a test cycle still requires 1-2 months. Neither of these methods can meet the needs of power systems for rapid detection and screening of substandard products. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides an accelerated corrosion solution and a method for detecting the resistance change rate and corrosion rate of flexible graphite grounding materials using the accelerated corrosion solution. The accelerated corrosion solution provided by this invention can accelerate the corrosion of flexible graphite grounding materials, enabling rapid evaluation of the corrosion resistance performance of different flexible graphite products.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0007] This invention provides an accelerated corrosion solution, comprising the following components by mass percentage:
[0008]
[0009] The remainder is distilled water.
[0010] The present invention also provides a method for detecting the resistance change rate and corrosion rate of flexible graphite grounding material using the aforementioned accelerated corrosion solution, comprising the following steps;
[0011] Test the resistance and mass of the flexible graphite grounding material under test;
[0012] The flexible graphite grounding material to be tested is immersed in the accelerated corrosion solution for corrosion, and then washed with water and dried to obtain the corroded flexible graphite grounding material.
[0013] During the immersion process, the temperature of the accelerated corrosion solution is 25–50°C; the immersion time is 8–15 hours.
[0014] Test the resistance and quality of corroded flexible graphite grounding materials;
[0015] Based on the resistance and mass of the corroded flexible graphite grounding material and the flexible graphite grounding material to be tested, the resistance change rate and corrosion rate of the flexible graphite grounding material to be tested are calculated.
[0016] Preferably, the drying temperature is 55–65°C and the drying time is 24–36 hours.
[0017] Preferably, the corrosion rate is calculated according to formula I:
[0018]
[0019] In Equation I, V is the corrosion rate, g / (dm³). 2 ·d);
[0020] Δm is the mass loss, in grams;
[0021] Δt is the reaction time, expressed in days (d).
[0022] A is the outer surface area of the sample to be tested, dm. 2 .
[0023] Preferably, the rate of change of resistance is calculated according to Equation II:
[0024] Resistance change rate = (resistance per unit length after reaction - resistance per unit length before reaction) / resistance per unit length before reaction × 100%; Equation II.
[0025] This invention provides an accelerated corrosion solution, comprising the following components by mass percentage: 2-7% HCl; 2-8% NaCl; 0.1-1% NaNO3; 1-3% K2S2O8; with the balance being distilled water. This invention utilizes an acidic medium, a substance containing Cl ions, and a strong oxidizing agent to optimize the corrosion solution. The optimized corrosion solution can accelerate the corrosion of flexible graphite grounding materials, providing a foundation for the rapid evaluation of the corrosion resistance of different flexible graphite products. Attached Figure Description
[0026] Figure 1 The morphology diagram is for 1-Cu.
[0027] Figure 2 The image shows the morphology of a 2-welded steel bar.
[0028] Figure 3 The morphology diagram is for 3-all-steel.
[0029] Figure 4 Morphological diagram of 4-graphite;
[0030] Figure 5 The morphological changes of 1-Cu, 2-silica, 3-all-steel, and 4-graphite after 1 hour of immersion are shown in the diagram.
[0031] Figure 6 In Figure a, the morphology of the internal copper wire before the 1-Cu accelerated corrosion test is shown, and in Figure b, the morphology of the internal copper wire after the 1-Cu accelerated corrosion test is shown.
[0032] Figure 7 Image a shows the morphology of the internal stainless steel before the accelerated corrosion test of 2-welded steel, and image b shows the morphology of the internal stainless steel after the accelerated corrosion test of 2-welded steel.
[0033] Figure 8 Image a shows the morphology of the internal stainless steel before the accelerated corrosion test of 3-all steel, and image b shows the morphology of the internal stainless steel after the accelerated corrosion test of 3-all steel.
[0034] Figure 9 Image a shows the morphology of the surface graphite before the 4-graphite accelerated corrosion test, and image b shows the morphology of the surface graphite after the 4-graphite accelerated corrosion test.
[0035] Figure 10In Figure a, the morphology of 1-Cu before the salt spray experiment is shown, and in Figure b, the morphology of 1-Cu after the salt spray experiment is shown.
[0036] Figure 11 In Figure a, the morphology of 2-coated steel before the salt spray test is shown, and in Figure b, the morphology of 2-coated steel after the salt spray test is shown.
[0037] Figure 12 Image a shows the morphology of the 3-all-steel steel before the salt spray test, and image b shows the morphology of the 3-all-steel steel after the salt spray test.
[0038] Figure 13 In Figure a, the morphology of the 4-graphite before the salt spray experiment is shown, and in Figure b, the morphology of the 4-graphite after the salt spray experiment is shown. Detailed Implementation
[0039] This invention provides an accelerated corrosion solution, comprising the following components by mass percentage:
[0040]
[0041] The remainder is distilled water.
[0042] In this invention, the accelerated corrosion solution preferably comprises the following components by mass percentage:
[0043]
[0044]
[0045] The remainder is distilled water.
[0046] The present invention also provides a method for detecting the resistance change rate and corrosion rate of flexible graphite grounding material using the aforementioned accelerated corrosion solution, comprising the following steps;
[0047] Test the resistance and mass of the flexible graphite grounding material under test;
[0048] The flexible graphite grounding material to be tested was immersed in an accelerated corrosion solution for corrosion, and then washed with water and dried to obtain the corroded flexible graphite grounding material.
[0049] Test the resistance and quality of corroded flexible graphite grounding materials;
[0050] Based on the resistance and mass of the corroded flexible graphite grounding material and the flexible graphite grounding material to be tested, the resistance change rate and corrosion rate of the flexible graphite grounding material to be tested are calculated.
[0051] This invention tests the resistance and mass of the flexible graphite grounding material to be tested, then immerses the flexible graphite grounding material to be tested in an accelerated corrosion solution for corrosion, and then washes it with water and dries it to obtain the corroded flexible graphite grounding material.
[0052] In this invention, during the immersion process, the temperature of the accelerated corrosion solution is preferably 25-50°C, more preferably 40°C; the immersion time is preferably 8-15 hours, more preferably 10 hours; and during the immersion process, the immersion corrosion morphology is preferably observed every 1-2 hours.
[0053] In this invention, the drying temperature is preferably 55-65°C, more preferably 60°C; the drying time is preferably 24-36 hours, more preferably 24 hours.
[0054] After obtaining the corroded flexible graphite grounding material, this invention tests the resistance and mass of the corroded flexible graphite grounding material. Based on the resistance and mass of the corroded flexible graphite grounding material and the flexible graphite grounding material to be tested, the resistance change rate and corrosion rate of the flexible graphite grounding material to be tested are calculated.
[0055] In this invention, the corrosion rate is preferably calculated according to Formula I:
[0056]
[0057] In Equation I, V is the corrosion rate, g / (dm³). 2 ·d);
[0058] Δm is the mass loss, in grams;
[0059] Δt is the reaction time, expressed in days (d).
[0060] A is the outer surface area of the sample to be tested, dm. 2 .
[0061] In this invention, the resistance change rate is preferably calculated according to Equation II:
[0062] Resistance change rate = (resistance per unit length after reaction - resistance per unit length before reaction) / resistance per unit length before reaction × 100%; Equation II.
[0063] Corrosion of grounding electrodes in the soil reduces their cross-sectional area and thermal stability over time, thus shortening their service life. Furthermore, the dense oxide layer formed on the surface of the grounding electrode due to corrosion, with low conductivity (such as oxides on aluminum grounding electrodes that are practically non-conductive), increases the grounding resistance of the grounding grid. Therefore, resistance change is used as an indicator to evaluate the degree of corrosion of grounding materials.
[0064] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0065] Example 1
[0066] Four types of flexible graphite grounding materials (denoted as 1-Cu, 2-hollowed steel, 3-all-steel, and 4-graphite) were selected for comparative research. 1-Cu was a 40×6mm flat strip with an outer graphite braided mesh and eight 2mm diameter copper-clad graphite wires in the middle. 2-hollowed steel was a 40×6mm flat strip with an outer graphite braided mesh and a 30mm wide, 1.5mm thick stainless steel hollow plate in the middle. 3-all-steel was a 40×6mm flat strip with an outer graphite braided mesh and a 30mm wide, 1.5mm thick solid stainless steel plate in the middle. 4-graphite was a 40×5mm flat strip with a full graphite braided mesh and no graphite or metal wires in the middle. Morphological images of 1-Cu, 2-hollowed steel, 3-all-steel, and 4-graphite are shown below. Figures 1-4 .
[0067] The resistance and mass of four types of flexible graphite grounding materials were tested respectively.
[0068] Four types of flexible graphite grounding materials were immersed in an accelerated corrosion solution at a temperature of 40°C for 10 hours, during which the immersion corrosion morphology was observed every hour.
[0069] After soaking for 10 hours, four types of flexible graphite grounding materials were taken out, washed with water, and dried at 60°C for 24 hours to obtain corroded flexible graphite grounding materials.
[0070] Test the resistance and quality of corroded flexible graphite grounding materials;
[0071] Based on the resistance and mass of the corroded flexible graphite grounding material and the flexible graphite grounding material to be tested, the resistance change rate and corrosion rate of the flexible graphite grounding material to be tested are calculated.
[0072] The corrosion rate is calculated according to Equation I, and the resistance change rate is calculated according to Equation II.
[0073]
[0074] In Equation I, V is the corrosion rate, g / (dm³). 2 ·d); Δm is the mass loss, g; Δt is the reaction time, d;
[0075] A is the outer surface area of the sample to be tested, dm. 2 ;
[0076] Resistance change rate = (resistance per unit length after reaction - resistance per unit length before reaction) / resistance per unit length before reaction × 100%; Equation II.
[0077] Before and after the accelerated corrosion test, the mass and resistance of the four flexible graphite grounding materials were compared. Based on the mass and resistance test values, the corrosion rate V and resistance change rate were calculated according to Equation I and Equation II, respectively. The test data and calculation results are shown in Table 1.
[0078] Table 1. Changes in mass and resistance during accelerated corrosion tests.
[0079] serial number 1-Cu 2-Hollowed Steel 3-All Steel 4-Graphite Mass before reaction / g 77.70 63.07 78.75 52.35 Mass after reaction / g 76.14 57.78 75.74 51.95 Change in mass / g -1.56 -5.29 -4.01 -0.40 <![CDATA[Corrosion rate / g / (dm 2 ·d)]]> <![CDATA[1.70×10 -1 ]]> <![CDATA[5.77×10 -1 ]]> <![CDATA[4.37×10 -1 ]]> <![CDATA[4.36×10 -2 ]]> Resistance per unit length before reaction / mΩ / cm 1.926 3.123 2.298 3.364 Resistance per unit length after reaction / mΩ / cm 2.099 3.413 2.571 3.568 Change in resistance per unit length / mΩ / cm 0.173 0.290 0.273 0.204 Rate of change of resistance 8.982% 9.268% 11.880% 6.064%
[0080] Figure 5 The graph shows the phase changes of 1-Cu, 2-silica, 3-steel, and 4-graphite after 1 hour of immersion. Figure 5 It was found that after immersion for 2 hours, small pores appeared in the stainless steel substrate inside the 2-wired steel and 3-all-steel samples, but they did not penetrate the steel plate. No significant changes were observed in other samples. After immersion for 5 hours, more small pores appeared in the stainless steel inside the 3-all-steel sample, and perforations appeared in the edge area. After 10 hours of accelerated corrosion testing, the graphite woven mesh on the surface of all four specifications of samples showed varying degrees of corrosion, with graphite flakes falling off and the internal glass fiber clearly exposed.
[0081] Figure 6 Image a shows the morphology of the internal copper wire before the 1-Cu accelerated corrosion test, and image b shows the morphology of the internal copper wire after the 1-Cu accelerated corrosion test; from Figure 6 It can be seen that after soaking for 10 hours, the surface color of the copper wire inside 1-Cu changed significantly, from the original yellow to reddish-brown, and verdigris formed in some areas.
[0082] Figure 7 Image a shows the morphology of the internal stainless steel before the accelerated corrosion test of the 2-welded steel, and image b shows the morphology of the internal stainless steel after the accelerated corrosion test of the 2-welded steel; from Figure 7 It can be seen that after soaking for 10 hours, dense pores appeared on the surface of the stainless steel inside the 2-hole steel, the steel sheet had a dull luster and obvious rust; indicating that the stainless steel reacted with the accelerated corrosion solution and the steel plate was corroded.
[0083] Figure 8 Image a shows the morphology of the internal stainless steel before the accelerated corrosion test of 3-all steel, and image b shows the morphology of the internal stainless steel after the accelerated corrosion test of 3-all steel; from Figure 8 It can be seen that after soaking for 10 hours, the stainless steel surface inside the 3-all-steel sample also showed significant defects, with densely distributed small holes and obvious rust.
[0084] Figure 9 Image a shows the morphology of the surface graphite before the 4-graphite accelerated corrosion test, and image b shows the morphology of the surface graphite after the 4-graphite accelerated corrosion test. Figure 9 It can be seen that after soaking for 10 hours, the graphite flakes on the surface of the 4-graphite fell off, and the internal glass reinforcing fibers were clearly exposed.
[0085] Comparative Example 1
[0086] The four flexible graphite grounding materials in Example 1 were subjected to salt spray tests. The salt spray tests were conducted on a salt spray machine produced by Shenzhen Zhongzheng Instrument Co., Ltd. The experimental conditions were as follows: 5% neutral saline (NaCl solution) spray, spray volume controlled at 1.0 mL / h, experimental pH 7.0, experimental temperature 35℃, and experimental time 30 days.
[0087] The morphological images of the four flexible graphite grounding materials before and after salt spray testing are shown below. Figures 10-13 ,in Figure 10 In Figure a, the morphology of 1-Cu before the salt spray experiment is shown, and in Figure b, the morphology of 1-Cu after the salt spray experiment is shown. Figure 11 In Figure a, the morphology of 2-coated steel before the salt spray test is shown, and in Figure b, the morphology of 2-coated steel after the salt spray test is shown. Figure 12 Image a shows the morphology of the 3-all-steel steel before the salt spray test, and image b shows the morphology of the 3-all-steel steel after the salt spray test. Figure 13 Image a shows the morphology of 4-graphite before the salt spray experiment, and image b shows the morphology of 4-graphite after the salt spray experiment. Figures 10-13 It was found that after 30 days of salt spray testing, the graphite flakes on the surface of the four types of flexible graphite samples detached in some areas of the graphite woven mesh, exposing the glass reinforcing fibers. The 1-Cu, 2-hollowed steel, and 3-all-steel samples not only showed changes in the surface graphite, but also exhibited varying degrees of corrosion in their internal metal substrate morphology. In the 1-Cu sample, the surface of the brass wire substrate changed from yellow to black, and obvious verdigris was observed in some areas. In the 2-hollowed steel sample, the surface of the hollowed-out steel plate substrate showed obvious damage and the formation of obvious brown rust. In the 3-all-steel sample, the stainless steel plate substrate also showed obvious damage and rust after the salt spray test. In the 4-graphite sample, which had no internal metal substrate, the graphite flakes on the surface of the graphite woven mesh detached in some areas after the salt spray test, exposing the glass reinforcing fibers.
[0088] Table 2 shows the comparison of the mass and resistance of the four flexible graphite grounding materials before and after the salt spray test.
[0089] Table 2 Comparison of mass and electrical resistance before and after salt spray test
[0090] serial number 1-Cu 2-Hollowed Steel 3-All Steel 4-Graphite Mass before reaction / g 88.60 60.80 80.33 44.00 Mass after reaction / g 88.47 60.48 79.82 43.86 Change in mass / g -0.13 -0.32 -0.51 -0.14 <![CDATA[Corrosion rate / g / (dm 2 ·d)]]> <![CDATA[1.97×10 -4 ]]> <![CDATA[4.85×10 -4 ]]> <![CDATA[7.73×10 -4 ]]> <![CDATA[1.94×10 -4 ]]> Resistance per unit length before reaction / mΩ / cm 1.926 3.123 2.298 3.364 Resistance per unit length after reaction / mΩ / cm 2.195 3.572 2.639 3.826 Change in resistance per unit length / mΩ / cm 0.269 0.450 0.3141 0.462 Rate of change of resistance 13.967% 14.409% 14.836% 13.734%
[0091] As shown in Table 2, 3-all steel and 2-wired steel have relatively fast corrosion rates, while the corrosion rates of 1-Cu and 4-graphite are not much different and are much smaller than those of the former two.
[0092] The resistance change rates before and after the salt spray test were all on the same order of magnitude. However, the 3-all-steel and 2-hollowed-steel samples, due to their embedded steel plates being relatively more susceptible to corrosion, showed a greater increase in resistance. In contrast, the 1-Cu sample, with its copper wire as the internal substrate, was less susceptible to corrosion, resulting in a smaller resistance change rate. The 4-graphite sample, being pure graphite, showed the smallest resistance change. Combining the corrosion rate and resistance change rate, it can be observed that materials with metallic internal substrates are more prone to corrosion, while pure flexible graphite without embedded materials exhibits the best corrosion resistance.
[0093] By comparing Example 1 and Comparative Example 1, it can be seen that the results of the accelerated corrosion test and the salt spray test are consistent. Furthermore, referring to Tables 1 and 2, the corrosion rate values of the accelerated corrosion test are significantly higher than those of the 30-day salt spray test, indicating that the accelerated corrosion test has a significant accelerating effect.
[0094] The resistance change rate remained consistent with the salt spray test results, and the resistance change rate value was on the same order of magnitude as that of the 30-day salt spray test. This indicates that using an accelerated corrosion solution to evaluate flexible graphite grounding materials has a certain degree of reliability, and it takes less time, is more convenient and faster, and can complete the evaluation of the corrosion resistance of different flexible graphite grounding materials within 10 hours.
[0095] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An accelerated corrosion solution, characterized in that: Calculated by mass percentage, it includes the following components: The balance is distilled water.
2. A method for detecting the resistance change rate and corrosion rate of a flexible graphite grounding material using the accelerated corrosion solution of claim 1, characterized in that: The steps include: Test the resistance and quality of the flexible graphite grounding material to be tested; The flexible graphite grounding material to be tested is immersed in the accelerated corrosion solution of claim 1 for corrosion, and then washed with water and dried to obtain the corroded flexible graphite grounding material; During the soaking, the temperature of the accelerated corrosion solution is 25 to 50° C.; the soaking time is 8 to 15 hours; Test the resistance and quality of corroded flexible graphite grounding materials; According to the resistance and mass of the corroded flexible graphite grounding material and the flexible graphite grounding material to be tested, the resistance change rate and the corrosion rate of the flexible graphite grounding material to be tested are calculated.
3. The method according to claim 2, characterized in that The drying temperature is 55-65° C. and the drying time is 24-36 hours.
4. The method according to claim 2, characterized in that The corrosion rate is calculated according to Formula I: In formula I, V is the corrosion rate, g / (dm 2 d); Δm is the mass loss, g; Δt is the reaction time, h; A is the surface area of the sample to be tested, dm 2 .
5. The method according to claim 2, characterized in that The resistance change rate is calculated according to Formula II: Resistance change rate = (resistance per unit length after reaction - resistance per unit length before reaction) / resistance per unit length before reaction × 100%; Formula II.
